Corpo re-moto controlado(r) - Ferreira, Maíra Spanghero (2005)
Remote Controlle(d, r) Body brings an original proposition to understanding the relationship between body and media, which is taken from studies in Communication, and developed from the theory in progress "Bodymedia". The hypothesis of this research says that bodies, while communicating, control and are remotely controlled while they manipulate any given media, (all kinds of media, including electronic and digital ones, like cell phone, computer, and television) technical tools, languages, ideas and other bodies. This is a relationship between organic and non-organic bodies, linked to nature s survival strategies. Bodymedia is the result of an interface between Philosophy of the Mind, Communication, Cognitive Sciences, Evolutionary Theories and Peirce's Semiotics. Its aim is to give support to understanding the body in the fields of Communication and Culture. Some of the points that form its interiority/structure, which are grounded in empirical facts are the relationship of co-determination between nature and culture, the relationship of co-determination between body and environment, the notion of the human within culture, the co-evolution and a singular understanding of the media. Emanating from these points of view, this project approaches metaphors relating to the pair body-technology, which are interlaced in cultural systems. Usually, studies relating to the body-machine point to a consolidation of the concept of the post-human. These studies lead to an updated mechanical and Cartesian point of view of the body. There is another line of investigation which leans to recent aspects of processes of subjectization related to new technologies and which frequently concentrate on the anthropomorphic direction of the discussion. Remote Controlle(d,r) Body indicates a different and not much explored viewpoint from those above-mentioned, when it proposes a new hypothesis on the interaction between body and media. It focuses the body movement as a thinking matrix and brings together two concepts: assimilation and anthropophagy (originally Brazilian). Both are proposed as useful tools for advancement in this area. Some of the objectives of this project are: to identify new conceptual strategies for the interaction between body and media, to present an original theoretical understanding of the body-machine, to introduce into the debate concepts of assimilation and anthropophagy and to collaborate in the construction of a theory that considers movement as a thinking matrix.